CHICKPEA AS A PROSPECTIVE LEGUME CROP FOR UKRAINIAN FOREST STEPPE - Холод, С. М.; Холод, С. Г.; Іллічов, Ю. Г. (Scientific Progress & Innovations, 2013)
Value of chickpea crop and the results of studies of 102 samples received from Syria based on the display of main economically valuable features are given in the article. Chickpea samples evaluation was done based on the processability and productivity and its components. Sources of economically valuable features were allocated according to following traits: seed productivity, number of seeds on a bean, number of beans on a plant, high weight of 1000 seeds and suitability for mechanical harvesting. Taking into consideration the results, these samples can be involved in breeding practice in order to increase productivity and processability under the conditions of southern Forest Steppe of Ukraine.